-18=p-12

Simple and best practice solution for -18=p-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=p-12 equation:


Simplifying
-18 = p + -12

Reorder the terms:
-18 = -12 + p

Solving
-18 = -12 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-18 + -1p = -12 + p + -1p

Combine like terms: p + -1p = 0
-18 + -1p = -12 + 0
-18 + -1p = -12

Add '18' to each side of the equation.
-18 + 18 + -1p = -12 + 18

Combine like terms: -18 + 18 = 0
0 + -1p = -12 + 18
-1p = -12 + 18

Combine like terms: -12 + 18 = 6
-1p = 6

Divide each side by '-1'.
p = -6

Simplifying
p = -6

See similar equations:

| .8x-1.3=2.5x+1.6 | | .50x+.35(50)=33.5 | | .8x+7.7=5.7 | | ax+2=bx-2 | | 3x+9=5n-1 | | .7(x+40)+1.1x=109 | | -d/16+12=-7 | | 57.2=2(6.7+2x)+2x | | 5.60+6.60(20)=4.25(x+20) | | .20x+.05(14-x)=.10(4) | | q=zd | | -d/16 | | -x^3-14x+35=0 | | (2x-15)+x=255 | | (2/3x) | | (2x-15)+x=225 | | (11/3/6)+1/3=(11/3/2)-8/9 | | 1/2(13-5)=1/5(13+2)+2 | | 117=13+2x | | 5x+25=10x | | 40+24(4)=30(x+4) | | (4x^2)-9x=-15 | | 27x+18= | | 0.4(2z+6)+11.2=0.6(2z-4) | | 0.6(x+200)=0.64x-184 | | xfois(17-2x)=21 | | 70-12b+12=10 | | 3.8x=2.8x+9.0 | | xX(17-2x)=21 | | 6x+7.2-2x=2.4 | | -10/-2=0 | | m-3/8=1/2 |

Equations solver categories